(3MeGjI GdQGgf Hjf GdbGfhf GdhVYj hGdTQjYI GdESdGejI (B:s (3OQGSI ebGQfI (B/ s - (3gGfj eMeO TYHGf MSfs; (3LGHQ eMLhH Ydis; (3eMeO YHO GdgGOj YHO GdSJGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3hef GdeYdhe Cf Pdc GdejQGK Gdabgj ddeSdejf bO oJQLe Edi ehGO OSJhQjI HOCJ aj YgO GdOhdI GdYKeGfjI HEUOGQ eLdI GdCMcGe GdYOdjI, Ke JWhQJ ajeG HYO JHYG dJWhQ GdYUhQ, hJYbjOGJ GdMjGI GdEOGQjI ajgG, hef Ke GSJMOKJ GdbhGfjf GdehLhOI MGdjG hGdJj JQGYj CMhGd GdfGS hWQb eYjTJge(B. (3hdeG cGfJ GdTQjYI eHfjI Ydi GdJjSjQ, hcGf GdEfSGf dG jedc ef GdeGd CMjGfG eG jecfg ef JdHjI GMJjGLGJg hJMbjb WehMGJg QNU dg GdTGQY aj Qgf eG jedc MJi jhSY Ydjg aj gPG GdLGfH, hdLC GdfGS Edi Qgf CUhdge Ch caGdI ZjQge dJMbjb eBQHge, aoTQY GdQgf dJMbjb eUdMI GdQGgf hGdeQJgf, ajMbb ddQGgf eG cGf jQei Edjg ef bQV, heG cGf jgOa Edjg ef GdTQGA Edi CnLd Yf WQjb Qgf Yjf eGdjI dOi GdeQJgf jSJWjY QOgG YfO GdhaGA HGdOjf GdeJab Ydjg ddeQJgf YfO Mdhd GdCLd GdeMOO, hjefM GdeQJgf GdKbI aj GdMUhd Ydi Ojfg EPG YLR GdeOjf, Ch GeJfY Yf GdhaGA, adG jNTi Ydi CehGdg fJjLI eSGYOI GdeMJGL(B. (3hQHeG jNTi UGMH GdeGd ef EYSGQ GdeOjf, ajDOi Edi GeJfGYg Yf EYWGA GdeGd HOhf hLhO VeGfGJ cGajI jSJQO HgG eGdg YfO JYPQ GdhaGA; aTQYJ GdcaGdI OaYG dPdc GdVQQ hVeGfG deUGdM GdYHGO JaQjLG ddcQhH hJNajaG ddgehe, hJMbjbG ddJYGhf ajeG Hjfge(B. (3hYdi GdQZe ef gPg GdahGFO GdJj JfWhj Ydi CgejI GdQgf, aEf GdQGgf bO jdMbg VQQ jahJ Ydjg GdeUdMI GdJj dLC Edi GdQgf ef CLdgG, hbO JJfhY gPg GdCVQGQ abO Jchf bHd EHQGe GdYbO Ch YfO EHQGeg Ch HYO EHQGeg, hef gfG HOJ CgejI GdHMK aj HjGf WQb MeGjI GdQGgf Hjf GdTQjYI hGdbGfhf(B. s
it is well known that this jurisprudential inheritance of Muslims has been translated into constitutional articles that began in the era of the Ottoman Empire with the issuance of the Journal of Justice Rulings, and then developed later according to the development of ages and the complexities of administrative life in it, and then the laws that currently exist were introduced that take into account the conditions of people and their ways of living. And since the Sharia is based on facilitation, and a person sometimes does not have enough money to meet his needs and achieve his aspirations, the Lawgiver authorized him to mortgage what he owns so that he can expand on it in this aspect, and people resorted to mortgaging their assets or guaranteeing others to achieve their goals. The mortgagor and the mortgagee, so the mortgagor achieves what he was aiming for in terms of a loan, and what he was aiming for in terms of buying on a deferred date by mortgaging a financial asset with the mortgagor, which he can return upon fulfillment of the debt agreed upon to the mortgagor when the specified term comes, and it gives the mortgagor confidence in obtaining his debt if the debtor is incapacitated. Or he refuses to pay, so he does not fear for his money as a result of helping the needy. Perhaps the owner of the money fears the insolvency of the debtor, and this leads to his refraining from giving the money without the presence of sufficient guarantees by which he will recover his money when payment is not possible. So the bail was prescribed to ward off that harm and guarantee the interests of the servants, relieving distress and alleviating worries, and achieving cooperation among them. In spite of these benefits that involve the importance of the mortgage, the mortgagor may suffer damage that makes him miss the interest for which he resorted to the mortgage, and these damages may vary, as they may be before the conclusion of the contract, when it is concluded, or after its conclusion. Protecting the present between Sharia and the law.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdeOfj, (B2023s
(3HHdjhLQGajG(B: (3UaMGJ (B280-258.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdejQGK Gdabgjs; (3YbO GdQgfs; (3GdYbGQ GdeQghfs; (3GdOjf GdeVehfs; (3GdTcdjI aj GdQgfs; (3GdQgf GdQSejs; (3GdQgf GdMjGRjs; (3GdMjGRI aj Gdefbhd SfO GdMGFRs; (3Jedc GdYbGQ GdeQghfs; (3Mb GdJbOe hGdJJHYs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs